Geospatial assessment of oil spill pollution in the Niger Delta of Nigeria: An evidence-based evaluation of causes and potential remedies - Akinwumiju, Akinola S.; Adelodun, Adedeji A.; Ogundeji, Seyi E. (Environmental pollution (1987), 2020)
Based on the archival data on oil facilities, oil spill incidents, and environmental conditions, we researched the plausible causes of oil spill disasters in the Niger Delta of Nigeria between 2006 and 2019. The data were analyzed for geospatial and statistical patterns, using ArcGIS and R programming platforms, respectively. A fuzzy logic algorithm was employed to generate three oil spill disaster models (hazard, vulnerability, and risk). Ordinary Least Square algorithm was adopted to model the relationships between oil spill and two sets of predictor variables: oil facilities (oil well, flow station, and pipeline) and disaster models. We found that, during the 23 years, the Niger Delta experienced 7940 oil spill incidents, of which 67% occurred onshore. A total of 4,950, 501, 855 episodes were attributed to sabotage, corrosion, and equipment failure, with 87%, 62%, and 45% occurring onshore, respectively. Besides, 81% of the 5320 onshore oil spill cases were attributed to sabotage, while corrosion and equipment failure accounted for mere 6% and 7% of the incidents, respectively. The estimated average risk index (R = 0.20) shows that the risk of an oil spill disaster in the Niger Delta is low. Whereas, 5% of the region is characterized by a high risk of oil spill disaster. Furthermore, the regression model infers that the oil spillages exhibit a positive relationship with disaster models and oil facilities at α = 0.10. However, only 16% of the incidents were explained by disaster models, while the oil facilities account for 23% of the total cases, indicating the influence of other factors. To avert further socio-environmental damage in the Niger-Delta, oil theft and sabotage should be curbed, polluted areas are remediated, and an all-inclusive socio-economic development is prioritized. [Display omitted] •Background information on the oil spill incidents in the Niger Delta is provided.•The hazard, vulnerability, and risk of oil spill cases are interrelated.•Most sabotage and equipment failure-based oil spill cases occurred onshore.•Most contaminated lands and swamps were in Rivers and Bayelsa States, respectively.•A +0.52 correlation exists between oil spill incidents and oil facilities.